Resource Productivity: Europe's Overlooked Route to Economic Security - Heather Grabbe (Intereconomics, 2025)
In its urgent search for critical raw materials, Europe is overlooking a key strategy: demand reduction by keeping resources in use for as long as possible. Given that its economy is more exposed to trade than the US and in a weaker geopolitical position, Europe needs to build on its strengths. It could achieve greater autonomy through circularity and sufficiency, most notably through eco-design, improved recovery of materials for secondary use and innovation. The EU's agendas for economic security, strategic autonomy and competitiveness would all benefit from a stronger circularity strategy.
Keywords: F43; Q56; Q26; 330